Estudo do comportamento de propagação de trincas por fadiga de ligas TiNbSn em função do teor de elementos de liga, deformação a frio e envelhecimento - Lima, Tiago Nunes (2017)
Titanium alloys are used for several applications of greater responsibility, for example in the biomedical, aeronautical, energy, security, among others sectors. Several studies have shown that TiNbSn alloys have advantages compared to other titanium alloys with respect to mechanical properties. Studies indicate a possibility of obtaining a tensile strength value as high as that of alloys traditionally used as Ti6Al4V, through cold deformation and aging. In addition, cold deformed TiNbSn alloys may have modulus of elasticity less than half the modulus presented by traditional alloys. These indications point to the possibility of intensifying the production and commercialization of TiNbSn alloys for the manufacture of highly responsible components. Therefore, for these applications, studies on the crack propagation behavior are important and even mandatory in certain circumstances, for example for the manufacture of components that may suffer catastrophic failures. The purpose of this study was to evaluate the fatigue crack propagation behavior of TiNbSn alloys system cold deformed and aged. In this study, the cold-rolled Ti35Nb2Sn, Ti42Nb2Sn and Ti42Nb alloys were produced with 80% true deformation and aged at 400 ° C for 48 hours. da/dN x ΔK tests were carried out and it was observed that the Ti422 and Ti420 alloys, both aged, had the best results of crack propagation resistance in the Paris regime and in the crack propagation threshold. That is, the increase of Niobium and the aging treatment produces alloy of greater crack propagation resistance. These results were attributed to the great cracks tortuosity. This tortuosity leads to a greater roughness induced crack closure effect. The threshold values increased with the aging process due to the increase in the modulus of elasticity values.